ANALYTICAL SOLUTION OF STRESS-STRAIN STATE OF LONG HOLLOW CYLINDER UNDER ACTION OF THERMAL RADIATION LOAD - I. S. Kulikov; S. A. Klus (Наука и техника)
The paper considers specific features of a stress-strain state of structure elements which have cylindrical form and which are subjected to the high temperature field, neutron irradiation. An analytical solution concerning displacement and stress dependences on a cylinder radius has been obtained and curve dependences have been constructed in the paper..